In which dialect was the Holy Qur’an revealed - Arpa, Abdulmuttalip; Arpa, Abdulmutalip (Necati Yıldız, 2017)
The question of in which dialect the Holy Qur’an was revealed has been a controversial issue among scholars. While the Qur’an’s being described within many verses in general as sent clearly in Arabic language so that it is understood and thought upon, led some of the scholars to the idea that it comprises all dialects of Arabic; on the other hand, the thought has arisen that it was revealed in the dialect of the Quraish as a result of some expressions within certain verses such as “We have sent every Messenger in the language of his people”, “We have made it (the Qur’an) easy in your language”. Furthermore, the fact that there are a number of loanwords in the Qur’an beside Arabic ones, led some –even if they are minority- to the idea that considering the universal message it carries, the Qur’an incorporates other languages apart from Arabic. This article, first of all, dwells upon the analysis of the concepts of language and dialect, the progress and the diversity of Arabic dialects, the influence of the Qur’an qiraats (recitations) on dialects, the dialect of the Quraish and the factors which made it prominent among others. Afterwards, being the main objective of this article, the subject of in which dialect the Qur’an was revealed is discussed and an evaluation is presented.

Kur’an’ı Kerim’in hangi lehçe ile nâzil olduğu hususu, âlimler arasında ihtilaf ko nusu olmuştur. Birçok ayette Kur’an’ın, anlaşılması ve üzerinde tefekkür edilmesi için apaçık Arap dili üzere nâzil oldu şeklinde genel olarak tavsif edilmesi, bir kısım ulemâ’yı onun Arapçanın tüm lehçelerine hâvî olduğu düşüncesine sevkederken; diğer taraftan bazı ayetlerdeki Biz her elçiyi kendi kavminin diliyle gönderdik; Biz O(Kur’an)nu senin diline kolaylaştırdık tarzı ifadeler, onun Kureyş lehçesi üzere nâzil olduğu düşüncesini doğurmuştur. Ayrıca Kur’an’da Arapça dışında birtakım yabancı kelimelerin bulunması azınlık da olsa bazı kimseleri Kur’an’ın evrensel mesajı da dikkate alınarak onun Arap çanın yanında başka dilleri de bünyesinde aldığı düşüncesine götürmüştür. İşte bu makalede öncelikle dil-lehçe kavramlarının analizi, Arap lehçelerinin gelişim ve çeşitliliği, Kur’an kıraatlerinin lehçeler üzerindeki etkisi, Kureyş lehçesi ve bu lehçe yi tüm lehçeler arasında öne çıkaran etkenler gibi konular üzerinde duruldu; ardından çalışmanın asıl amacını teşkil eden Kur’an’ın nâzil olduğu lehçe konusu ele alınıp-tartı şılarak bir değerlendirmeye gidildi.
Kur’an-ı Kerim hangi lehçe ile nâzil oldu
Keywords: Kur’an; Dil; Lehçe; Kureyş lehçesi; Qur’an; Language; Dialect; Quraishî Dialect; Arabic Language